CULTURAL RELATIONS OF THE KOKAN KHAN AND ITS REFLECTION IN THE MUSEUM EXPOSITION: ANALYSIS AND PRINCIPLES (TAMADDUN NURI JURNALI, 2025)
This article explores the place of the Kokand Khanate culture in the context of international cultural exchanges, systematically analyzes how these processes are reflected in museum expositions, and introduces new approaches to exposition activities to interpret historical heritage as an active tool in the formation of collective consciousness and cultural identity.